2022
DOI: 10.3390/antibiotics11010075
|View full text |Cite
|
Sign up to set email alerts
|

Guideline Adherence of Asymptomatic Bacteriuria Could Be Improved among General Practitioners in The Netherlands: A Survey Study

Abstract: Asymptomatic bacteriuria (ASB) is a common finding in certain populations. This study assessed general practitioners’ (GPs’) knowledge about ASB and their current clinical practice regarding urine testing. Methods: An online survey was used for GPs in the Netherlands from October to December 2020. Results: In total, 99 surveys were included in the analyses. All GPs strongly agreed with the statements about their knowledge and self-confidence regarding urine diagnostics and treatment of ASB. The median knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Results showed that most GPs followed their national guideline regarding UTIs, but knowledge about asymptomatic bacteriuria could be improved. 13 Not all RDs are involved in a patient population that requires an IC or CIC which can explain a lower number of respondents in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that most GPs followed their national guideline regarding UTIs, but knowledge about asymptomatic bacteriuria could be improved. 13 Not all RDs are involved in a patient population that requires an IC or CIC which can explain a lower number of respondents in this field.…”
Section: Discussionmentioning
confidence: 99%